2017
DOI: 10.1175/jcli-d-16-0497.1
|View full text |Cite
|
Sign up to set email alerts
|

Sea Level Variability around Japan during the Twentieth Century Simulated by a Regional Ocean Model

Abstract: Sea level variability around Japan from 1906 to 2010 is examined using a regional ocean model, along with observational data and the CMIP5 historical simulations. The regional model reproduces observed interdecadal sea level variability, for example, high sea level around 1950, low sea level in the 1970s, and sea level rise during the most recent three decades, along the Japanese coast. Sensitivity runs reveal that the high sea level around 1950 was induced by the wind stress curl changes over the North Pacifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 49 publications
1
12
1
Order By: Relevance
“…Notably, the MSL rise in R3 (+24.3 mm year -1 ) is larger than in the other regions, whereas no compound effect is noticeable as of R1 and R2. Several previous works have shown that MSL is rising along the Japanese coast (24)(25)(26), nevertheless, we report the compound effect of storm surge and MSL change for the first time.…”
Section: Observational Evidence Of Storm Surge Changecontrasting
confidence: 48%
“…Notably, the MSL rise in R3 (+24.3 mm year -1 ) is larger than in the other regions, whereas no compound effect is noticeable as of R1 and R2. Several previous works have shown that MSL is rising along the Japanese coast (24)(25)(26), nevertheless, we report the compound effect of storm surge and MSL change for the first time.…”
Section: Observational Evidence Of Storm Surge Changecontrasting
confidence: 48%
“…This coincides with the 10‐5 years long period of 7 cm RSL drop recorded by corals microatolls between 1950 and 1960‐968 (Figure ). As well, a decadal regional sea‐level drop is found at the same time in tide gauge records from Japan mainland (Sasaki et al, ) that would reflect multidecadal sea‐level oscillations driven by climate variability. Indeed, the work of Meyssignac et al () highlighted that regional sea‐level trend patterns are not long‐lived features.…”
Section: Rsl Changes Pattern At Regional Scalementioning
confidence: 78%
“…Sasaki et al (2014) stress the importance of understanding the dynamical reasons for such variability in order to reliably predict future sea level changes. In a later modelling study of Japan sea level variability over 1906, Sasaki et al (2017 further pointed to the need to understand natural variability on decadal timescales for understanding future regional sea level change.…”
Section: (A) (B)mentioning
confidence: 99%